Development of Interactive E-Module with Realistic Mathematics Education (RME) Approach to Increase Numeracy Skills and Mathematical Growth Mindset - Vevi Arini Azizatus Sufaidah; Ariyadi Wijaya (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research aims to: (1) produce mathematics learning media in the form of interactive e-modules with a learning approach.realistic mathematics education (RME) which is oriented towards numerical ability and mathematical growth mindset students and describe their characteristics; (2) describe the quality of the learning e-module which meets the criteria of being valid, practical and effective so that it is suitable for use by junior high school students using the approach realistic mathematics education (RME). The development model used in this development research is the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects consisted of one teacher and 32 seventh grade students of SMP Negeri 3 Pajangan in Bantul Regency, Yogyakarta, who participated in this research.The results of the study show that the developed e-module has the following main characteristics: (1) using the RME approach in learning strategies; (2) facilitating the improvement of numeracy through learning videos, LKPD, and quizzes; (3) fostering growth mindset through motivational videos, inspirational sentences, discussion spaces, as well as feedback and self-evaluation features; and (4) using test- and questionnaire-based evaluation instruments. Validity tests showed very good results with an average score of 96% from media experts and 98% from material experts. The practicality of the e-module was assessed as very good by teachers (96.19%) and good by students (80.47%), and the implementation of learning reached 96.8%. Effectiveness was proven through MANOVA and t-tests which showed a significant increase in numeracy and mathematical growth mindset after using the e-module. Thus, the RME-based interactive e-module is suitable for use as an innovative mathematics learning medium at the junior high school level.